MENGUKUR POTENSI UMKM KERUPUK MELALUI PENDEKATAN TEKNO-EKONOMI UNTUK PERTUMBUHAN BISNIS BERKELANJUTAN - Komari, Ana; Indrasari, Lolyka Dewi; Tripariyanto, Afiff Yudha; Djayadi, Djohan; Mustofa, Faisal (Universitas Putera Batam, 2024)
The dynamic competitiveness requires White Cracker MSMEs in Kediri to evaluate their Net Present Value, Internal Rate of Return, Payback Period, and Profitability Index. The assessment carried out at this level is to produce value standardization for the progress of these MSMEs. The findings show that the NPV exceeds Rp. 143,316,000, the IRR is above 50%, the PBP is less than 7 months 9 days, and the PI is greater than 1.00. This indicates that the white cracker MSME business has strong development potential and offers profitable returns for the owners. The profit potential is good for the white cracker MSME business. However, the quality of products with good taste and in accordance with consumer needs is important to build customer loyalty. Strength Strategy – Opportunity to use Unique Products-Digital innovation marketing components, Kediri original product market potential-Products that are attractive to tourists visiting Kediri and the latest taste tests for consumers-Different taste innovations from 1 product. Strict product development and quality control are carried out in order to always be of high quality and meet consumer expectations.